2023
DOI: 10.21873/cdp.10251
|View full text |Cite
|
Sign up to set email alerts
|

The Number of Colon Crypts in Digital Mucosal Samples: A New Independent Parameter for Diagnosing Ulcerative Colitis

CARLOS A. RUBIO,
CORINNA LANG-SCHWARZ,
CHRISTIAN MATEK
et al.

Abstract: Background/Aim: It has been demonstrated that most routine biopsies from the colon and rectum display cross-cut crypts (CCC). The aim was to assess the number of CCC in microscopic isometric digital samples (0.500 mm2) from routine colon biopsies. Patients and Methods: Colon biopsies from 224 patients were investigated: 99 in patients with ulcerative colitis (UC), 31 UC in remission (UCR), 28 infectious colitis (IC), 7 resolved IC (RIC), 19 diverticular sigmoiditis (DS), and 40 normal colon mucosa (NCM). Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…A series of studies, mainly conducted by Rubio and coworkers, has underlined the importance of crypt asymmetrical branching of regenerating crypts after chronic neutrophil-driven damage as an instrument for a more precise definition of crypt distortion [17,18]. Recently, the same group demonstrated that specimen orientation could represent a bias in crypt morphology evaluation; a significant portion of the histologic section that resulted in a diagnosis of IBD held cross-cut crypts, an inappropriate sectioning plane that modifies the correct assessment of the other histological parameters that defined the diagnosis of IBD [19][20][21]. On the other side, a series of cryptassociated anomalies were described in addition to crypt branching in crypt destructive inflammations that should be considered in their assessment on histologic slides [22].…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies, mainly conducted by Rubio and coworkers, has underlined the importance of crypt asymmetrical branching of regenerating crypts after chronic neutrophil-driven damage as an instrument for a more precise definition of crypt distortion [17,18]. Recently, the same group demonstrated that specimen orientation could represent a bias in crypt morphology evaluation; a significant portion of the histologic section that resulted in a diagnosis of IBD held cross-cut crypts, an inappropriate sectioning plane that modifies the correct assessment of the other histological parameters that defined the diagnosis of IBD [19][20][21]. On the other side, a series of cryptassociated anomalies were described in addition to crypt branching in crypt destructive inflammations that should be considered in their assessment on histologic slides [22].…”
Section: Discussionmentioning
confidence: 99%